ANALISIS EFEKTIVITAS PENGGUNAAN MODAL KERJA PADA PT. FRESMON PACIFIK PRIMA DI SAMARINDA - Rachmawati, Endah (EKONOMIA, 2013)
The purpose of this paper is to analyze the effectiveness of the use of working capital in PT. Fresmon Pacific Prima in Samarinda, in 2009 until 2012.For the purposes of this paper, the main issues raised